Experiential Marketing and E-Wom Create Brand Loyalty Through Brand Trust - Aminudin Azis; Ina Syarifah; Netty Lisdiantini (Jurnal Multidisiplin Madani, 2023)
This study examines and explains the relationship of variables that become income factors from the application of marketing concepts, namely experiential marketing, E-WOM, Brand Trus, which then form brand loyalty. The object of this research is a hotel in Malang. The data was obtained by distributing online questionnaires to 160 people. Furthermore, the data were analyzed using the Partial Leasr Square (PLS) analysis tool with SmartPLS software. The results of this study indicate that; first, experiential marketing has a significant positive effect on brand trust, the second experiential marketing has a significant positive effect on brand trust, the third experiential marketing has a significant positive effect on brand loyalty, the fourth E-WOM has a significant positive effect on brand loyalty and fifth, brand trust has a significant positive effect on brand loyalty